2008
DOI: 10.1038/nprot.2008.31
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of fluorescent markers in confocal microscope images of plant cells

Abstract: This protocol describes the steps needed to perform quantitative statistical colocalization on two-color confocal images, specifically of plant cells. The procedure includes a calibration test to check the chromatic alignment of the confocal microscope. A software tool is provided to calculate the Pearson and Spearman correlation coefficients ('Pearson-Spearman correlation colocalization' ImageJ plug-in) across regions of interest within the image. Steps are included to help the user practice using the softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
328
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(332 citation statements)
references
References 20 publications
2
328
0
2
Order By: Relevance
“…As shown in Figures 5A to 5C, the punctate compartments of GPA3-GFP were obviously distinct from the Golgi but partially overlapped with the TGN and PVC. Furthermore, correlation analysis using the Pearson-Spearman correlation (PSC) plugin for ImageJ (French et al, 2008) revealed strong correlation between GPA3-GFP and the PVC marker (r s = 0.646), but the correlation between GPA3-GFP and the TGN marker appeared to be weaker (r s = 0.194).…”
Section: Gpa3 Protein Is Localized To Post-golgi Compartmentsmentioning
confidence: 99%
“…As shown in Figures 5A to 5C, the punctate compartments of GPA3-GFP were obviously distinct from the Golgi but partially overlapped with the TGN and PVC. Furthermore, correlation analysis using the Pearson-Spearman correlation (PSC) plugin for ImageJ (French et al, 2008) revealed strong correlation between GPA3-GFP and the PVC marker (r s = 0.646), but the correlation between GPA3-GFP and the TGN marker appeared to be weaker (r s = 0.194).…”
Section: Gpa3 Protein Is Localized To Post-golgi Compartmentsmentioning
confidence: 99%
“…Image analysis was undertaken using the ImageJ analysis program (Abramoff et al, 2004) using the PSC co-localization plug-in (French et al, 2008) to calculate co-localization. At least 20 cells were analysed for each condition.…”
Section: Location Of Dengue Virus Replication Complexmentioning
confidence: 99%
“…Co-localization was quantified using Pearson's co-localization coefficient, which assesses the strength of linear correlation between pixel fluorescence in two different channels. 11 indicates perfect co-localization, a value of zero indicates no co-localization, and À1 indicates a perfect negative correlation between the intensities in the two channels [20].…”
Section: Nuclear Retention Of Il-1a By Immobilizationmentioning
confidence: 99%
“…Pearson's co-localization analysis was used to assess the co-localization of IL-1a-GFP with nuclear proteins and DAPI [20].…”
Section: Confocal Microscopy and Frapmentioning
confidence: 99%
See 1 more Smart Citation